Optimal Capital Structure Analysis of PT Kencana Energi Lestari Tbk - Setiawan, Zefania (Integrasi Sains Media, 2023)
In 2020, fossil fuels accounted for around 80% of the world's energy supply, but the 2022 global energy crisis highlighted their vulnerability and lack of sustainability, prompting a global shift towards renewable energy sources. Indonesia, recognizing its potential in renewable energy, has taken proactive steps to accelerate its transition, such as the issuance of Peraturan Presiden Nomor 112 Tahun 2022 to facilitate renewable energy development. PT Kencana Energi Lestari Tbk responded positively to the regulation and has allocated USD 30 million in 2023 to implement renewable energy strategies. They are also pursuing a USD 100 million renewable energy project in the Philippines. To fund its initiatives, PT Kencana Energi Lestari Tbk plans to use USD 9 million from internal cash reserves and obtain an additional USD 121 million from external financing sources. However, their current capital structure has a debt-to-equity ratio of 76.84%, which deviates significantly from the industry average of 35.92%, suggesting that it may not be optimal. This study employs the Weighted Average Cost of Capital (WACC) method to identify the most optimal capital structure that will maximize the company's value. The suggested capital structure consists of 34% debt and 66% equity, resulting in an optimal cost of capital of 12.2868%. To implement their renewable energy plan, PT Kencana Energi Lestari Tbk needs to secure a total funding of USD 23,947,572.54 through debt financing and USD 97,052,427.46 through equity financing. Keywords: optimal capital structure; renewable energy; financing plan